Fat globule size and distribution in milk and iodine value of milk fat of Vechur cattle of Kerala - VENKATACHALAPATHY, R THIRUPATHY; IYPE, SOSAMMA (The Indian Journal of Animal Sciences, 2013)
Vechur cows (15) were used for this study. The size and distribution offat globules were studied at weekly intervals in the morning and evening milk samples from individual cows for 40 weeks of lactation. The iodine value of milk fat was estimated at fortnightly intervals for 9 fortnights. The mean diameter of fat globules is 3.02 in the evening and the average of morning and evening is 3.21 . The average size ranged from 2.54 to 3.73 in the morning and 2.75 to 4.07 in the evening milk. The average size was uniformly higher in the evening milk from I to 40 weeks of lactation than in the morning. A general decreasing trend was noticed in average size and proportion of large size fat globules as lactation advanced. The mean iodine value was 29.60+- 2.20 with a range from 28.61 to 30.26. This study indicates that the milk of Vechur cow is different from other breeds of cattle with respect to fat globule size and iodine value.